2015
DOI: 10.1002/iid3.87
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐25 initiates Th2 differentiation of human CD4+ T cells and influences expression of its own receptor

Abstract: Human CRTh2+ Th2 cells express IL‐25 receptor (IL‐25R) and IL‐25 has been shown to potentiate production of Th2 cytokines. However, regulation of IL‐25R and whether it participates in Th2 differentiation of human cells have not been examined. We sought to characterize IL‐25R expression on CD4+ T cells and determine whether IL‐25 plays a role in Th2 differentiation. Naïve human CD4+ T cells were activated in the presence of IL‐25, IL‐4 (Th2 conditions) or both cytokines to assess their relative influence on Th2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…65 In addition to amplifying established T H 2 responses, IL-25 acts directly on naive human CD4 + T cells to induce T H 2 differentiation, although not to the same extent as the prototypical T H 2-differentiating cytokine IL-4. 66 IL-25 also mirrors the direct effects of IL-33 on memory T H 2 cells in the context of chronic rhinosinusitis. 62 These actions, coupled with an association between IL-25 and T H 2-high asthma, 67 support a pathogenic role for IL-25 in T H 2-driven airway disease resembling that of IL-33.…”
Section: Tslpmentioning
confidence: 84%
“…65 In addition to amplifying established T H 2 responses, IL-25 acts directly on naive human CD4 + T cells to induce T H 2 differentiation, although not to the same extent as the prototypical T H 2-differentiating cytokine IL-4. 66 IL-25 also mirrors the direct effects of IL-33 on memory T H 2 cells in the context of chronic rhinosinusitis. 62 These actions, coupled with an association between IL-25 and T H 2-high asthma, 67 support a pathogenic role for IL-25 in T H 2-driven airway disease resembling that of IL-33.…”
Section: Tslpmentioning
confidence: 84%
“…Levels of both IL-25 and IL-17RB mRNA and protein increase in the lungs after infection with respiratory syncytial virus or rhinovirus 35,47 or after allergen exposure, as shown in the present study and in a previous study. 4 IL-25 was shown to induce IL-17RB surface expression by human CD4 1 T cells, 48 and IL-17RB expression by human monocytic cells was induced and amplified by IL-4 and IL-25. 49 We found that although about 50% of the RGMb 1 interstitial macrophages taken directly from inflamed lungs expressed IL-17RB, on incubation with rIL-25, expression increased to greater than 98%.…”
Section: Discussionmentioning
confidence: 98%
“…To directly compare the ability of dexamethasone and prednisolone to suppress type 2 cytokine production, primary Th2 cells (Supplemental Figure 1 (Figure S1)) [42,43] cultured in IL-2 (4 days) were treated (24 hours) with equimolar concentrations of either CS (10 -9 -10 -7 M) as in [15,18]. Moreover, these concentrations are within the pharmacological range [44].…”
Section: Dexamethasone More Potently Reduces Type 2 Cytokine Levels Tmentioning
confidence: 99%
“…Cytokine expression Intracellular staining to characterize primary Th2 cells was previously described in [42,43]. Brie y, cytokine staining for IL-4, IL-13 and IFNγ was performed following 4 hours of stimulation with PMA (20ng/mL) and ionomycin (1 μM) in the presence of Brefeldin A (10 μg/mL, all from Sigma Aldrich, Canada).…”
Section: Flow Cytometrymentioning
confidence: 99%